Studies on a family of beetles. The Carabidae - Wheeler, George Carpenter (My University, 1895)
Introduction: The following paper is the result of my studies upon the family of beetles commonly known as the ground beetles, or the Carabidae of scientific entomologists. My study has been comparatively very limited and no attempt has been made to make an exhaustive treatise of the subject. It would require much longer time and more space than the paper will cover. In treating the subject those characters have been emphasized which seem of most primary importance, and the genera and species studied specially and to which the most time has been given are those which in my mind are the best types of the family and its subdivisions, a part of the drawings presented are taken from the result of studies of my own specimens and such as are not are taken from the plates which Dr. George H. Horn prepared as the results of his dissections in the study of this family. Some have also been taken from the dissections of C. V. Riley and others. The family Carabidae is a very extensive one and the limits are not easy to define. It is one of the adephagous series of coleoptera of which six families are represented in our fauna. The series may be easily recognized by the predaceous mouth parts, slender antennae, five jointed tarsi, and the structure of the first abdominal segment, which is only visible at the sides, being divided by the posterior coxa. The last character is an important one and runs through the whole series.
Citation: Wheeler, George Carpenter. Studies on a family of beetles. The Carabidae. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Entomology; Ground beetles; Carabidae; Drawings; Theses; Manuscripts (documents)